Analisis Kemampuan Pemecahan Masalah Matematika pada Operasi Bilangan Bulat Siswa Kelas VI SD - Ramadhan, Alif Akbar Bayu; Maulana, Maulana; Isrok’atun, Isrok’atun (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the ability to solve mathematical problems in integer operation materials. This qualitative descriptive research involved 27 students of grade VI B SD Taman Kalijaga Permai who were selected based on the results of the mathematics problem-solving ability test and teacher consideration. The research instruments used included problem-solving skills tests and interviews. Data analysis uses Miles and Huberman's interactive model which includes data reduction, data presentation, and conclusion drawn. The results showed that students in the high category consisting of 5 out of 5 students (100%) could understand and determine the information in the problem well. Then, students with moderate problem solving ability 8 out of 14 (57%) used a complete presentation of information while 6 out of 14 (43%) only wrote the final calculation and low category students consisting of 3 out of 8 students (37.5%) did not write down the solution information in detail and 5 out of 8 students (62.5%) explained the calculation steps but there were still errors in the operation of negative signs or inaccuracy of numbers. Based on these data, it shows that the problem solving ability of grade VI students of SD Taman Kalijaga Permai has varying abilities, depending on the level of ability of each student but can solve problems correctly and provide conclusions for each problem worked out